Framework to study the requirements-driven collaboration in agile teams / Irum Inayat - Irum, Inayat (2015)
Requirements engineering requires intensive collaboration among team members. The importance of collaboration in agile methods is also undeniable. Due to their emphasis on collaboration, agile methods and requirements engineering activities seem to mutually support each other in software development. However, very little is still known about the “agile way” of dealing with requirements and how collaboration driven by requirements takes place especially among distributed team members. The main aim of this research is to investigate the socio-technical aspects of requirements-driven collaboration in agile teams. Firstly, this research identified the most relevant socio-technical aspects of` requirements-driven collaboration among agile teams through an online survey conducted on industry practitioners, as communication and awareness. Secondly, a framework was proposed to study the identified socio-technical aspects of requirements-driven collaboration among agile teams and a prototype was developed to partially automate the framework. Thirdly, an empirical investigation was conducted by studying four IT-based projects carried out in four different organizations. This empirical investigation led to the practical implementation of the proposed framework to study the requirements-driven collaboration among agile teams. This research was validated from two perspectives. From the academic perspective, the results show that the framework is structurally acceptable. From the industrial perspective, an applicability validation was performed to assess the application of the proposed framework while a utility validation was conducted to gauge the usefulness of the proposed framework. The study provides implications for both research and industry practitioners in the form of further research and tool development for agile teams collaboration and performance analysis underlying the concepts proposed in this study.